TCAD RF performance investigation of Transparent Gate Recessed Channel MOSFET. (March 2016) - Kumar, Ajay; Gupta, Neha; Chaujar, Rishu
Abstract: In this paper, analog/RF performance and small signal behavior of Transparent Gate Recessed Channel (TGRC) MOSFET has been investigated in terms of transconductance, DIBL, channel resistance parasitic capacitances, cut-off frequency and maximum oscillator frequency. Results so obtained are compared with Conventional Recessed Channel (CRC) MOSFET at THz frequency range, using ATLAS-3D device simulator. Furthermore, the impact of technology parameter variations in terms of gate length ( L g ) has also been evaluated. Result shows that there is 42% enhancement in cut-off frequency, 132% increment in maximum oscillator frequency and significant improvement in parasitic capacitances for TGRC-MOSFET due to reduced short channel effects (SCEs) and enhanced on-current driving capabilities thus, reflecting its significance in high-frequency THz range applications. Highlights: TGRC-MOSFET improved analog and RF performance at THz frequency range. Enhancement in transconductance, reduction in parasitic capacitances and reduction in SCEs such as DIBL is observed. Improvement is perceived both in reflection and transmission coefficients as compared to CRC-MOSFET. 42% Enhancement in cut-off frequency, 132% increment in maximum oscillator frequency is observed. TGRC-MOSFET is appropriate for high-performance System-On-Chip RF/microwave applications.